Structural and dynamic aspects of Ca2+ and Mg2+ binding of the regulatory domains of the Na+/Ca2+ exchanger. (21st March 2012) - Breukels, Vincent; Touw, Wouter G.; Vuister, Geerten W.
Abstract : Intracellular Ca 2+ regulates the activity of the NCX (Na + /Ca 2+ exchanger) through binding to the cytosolic CBD (Ca 2+ -binding domain) 1 and CBD2. In vitro studies of the structure and dynamics of CBD1 and CBD2, as well as studies of their kinetics and thermodynamics of Ca 2+ binding, greatly enhanced our understanding of NCX regulation. We describe the fold of the CBDs in relation to other known structures and review Ca 2+ binding of the different CBD variants from a structural perspective. We also report on new findings concerning Mg 2+ binding to the CBDs and finally we discuss recent results on CBD1–CBD2 interdomain interactions.